The Use of Macromedia Flash Application in Improving the Mathematical Understanding of Elementary School Students - Firdaus, Fery Muhamad; Afianti, Dika; Cahya, Rizki; Septianingtias, Arina (Jurnal Prima Edukasia, 2022)
Mathematics learning will run optimally if it is supported by the use of learning media in accordance with learning objectives and student needs. One of them is the application of learning media through Macromedia Flash to improve students' mathematical understanding. This type of research is classroom action research (Classroom Action Research). This research was conducted in class V of MI Al Washliyah Jangungan in the even semester of the 2020/2021 school year. The subjects of this study were students of class V with a total of 16 children. The object of this research is the learning process by applying learning media based on Macromedia Flash. The results of this study indicate that the application of learning media based on Macromedia Flash 8 in building materials is able to improve students' mathematical understanding with a percentage of 94% of 16 students, which can be categorized in the "Very Strong" category. His learning outcomes also increased from the average value of 80.4 in cycle 1 to 87,625 in cycle 2 and was declared "Completed".